Investigations into small-dose ingredients for human performance and recovery - Durkee, S. E.; Saiyed, Z. M. (Nature, 2021)
Lonza Consumer Health Inc. is a leading global provider of integrated nutraceutical solutions, which seeks to drive the fields of health and human performance through advances in nutritional science, breakthroughs in performance, and the courage to raise the physical standards of humanity through the provision of small-dose supplements. Outlined here are Lonza`s unique insights into recent breakthroughs in small-dose sports nutrition ingredients that show promising effects on endurance, recovery, and strength. Over the past few decades, a variety of people have driven the boundaries of human performance forward at a rate that exceeds any ever witnessed. This revolution has occurred in a virtual blink of an eye, and it has redefined the limits of possibility. Though these advances have taken place in front of millions, it can still be difficult to comprehend. Beyond running faster and jumping higher, humans are riding 100-foot waves, jumping from 100-foot cliffs and performing unfathomable stunts. According to Jacob M. Wilson, CEO of the Applied Science and Performance Institute, a sports science facility in Tampa, Florida, "What appears to defy reality is actually gradual. Behind seemingly impossible feats is a series of small steps driven by elite physical training, nutrition, technology, innovation, grit, and fortitude."